Separation of church and state - Hamburger, Philip (Harvard University Press, 2020)
In a powerful challenge to conventional wisdom, Philip Hamburger argues that the separation of church and state has no historical foundation in the First Amendment. The detailed evidence assembled here shows that eighteenth-century Americans almost never invoked this principle. Although Thomas Jefferson and others retrospectively claimed that the First Amendment separated church and state, separation became part of American constitutional law only much later. Hamburger shows that separation became a constitutional freedom largely through fear and prejudice. Jefferson supported separation out of hostility to the Federalist clergy of New England. Nativist Protestants (ranging from nineteenth-century Know Nothings to twentieth-century members of the K.K.K.) adopted the principle of separation to restrict the role of Catholics in public life. Gradually, these Protestants were joined by theologically liberal, anti-Christian secularists, who hoped that separation would limit Christianity and all other distinct religions. Eventually, a wide range of men and women called for separation. Almost all of these Americans feared ecclesiastical authority, particularly that of the Catholic Church, and, in response to their fears, they increasingly perceived religious liberty to require a separation of church from state. American religious liberty was thus redefined and even transformed. In the process, the First Amendment was often used as an instrument of intolerance and discrimination.[Pt.] I. Late eighteenth-century religious liberty. Separation, purity, and anticlericalism -- Accusations of separation -- The exclusion of the clergy -- Freedom from religious establishments. [Pt.] II. Early nineteenth-century republicanism. Demands for separation: separating Federalist clergy from Republican politics -- Keeping religion out of politics and making politics religious -- Jefferson and the Baptists: separation proposed and ignored as a constitutional principle. [Pt.] III. Mid-nineteenth-century Americanism. A theologically liberal, anti-Catholic, and American principle -- Separations in society -- Clerical doubts and popular Protestant support -- [Pt.] IV. Late nineteenth- and twentieth-century constitutional law. Amendment -- Interpretation -- Differences -- An American constitutional right.